Mathematical modelling and analysis of emergencies in break of pipeline - Гусарова, Ирина Григорьевна; Каминская, Анна Владимировна (Eastern-European Journal of Enterprise Technologies, 2012)
The article presents a mathematical modeling of non-stationary modes of the multi-threads linear sections of gas transport system at break of the pipeline and proposes the method for detecting breaks sections of the pipeline.